2014
DOI: 10.1002/pd.4479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of labor on plasma concentrations and postpartum clearance of cell-free, pregnancy-associated, placenta-specific microRNAs

Abstract: The presence of labor affects cell-free, pregnancy-associated, placenta-specific miRNA levels in maternal plasma. Labor also affects postpartum clearance of these miRNAs 24 h after delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
(65 reference statements)
1
15
0
Order By: Relevance
“…miRNA profiles in amniotic fluid reveal their involvement in pathways (such as axon guidance, focal adhesion, and mitogen-activated protein kinase signaling pathways) related to the normal development of the nervous system and other organs (Figure 1) [52]. Even though the effect of labour on miRNA profiles has been reported in plasma, miRNA profiles have yet to be identified in milk or amniotic fluid based on vaginal or caesarean-section modes of delivery [53]. The mode of delivery has been shown to affect the bacterial presence and abundance in human milk [54].…”
Section: New Kids On the Block: Mirnas Really Do Mattermentioning
confidence: 99%
“…miRNA profiles in amniotic fluid reveal their involvement in pathways (such as axon guidance, focal adhesion, and mitogen-activated protein kinase signaling pathways) related to the normal development of the nervous system and other organs (Figure 1) [52]. Even though the effect of labour on miRNA profiles has been reported in plasma, miRNA profiles have yet to be identified in milk or amniotic fluid based on vaginal or caesarean-section modes of delivery [53]. The mode of delivery has been shown to affect the bacterial presence and abundance in human milk [54].…”
Section: New Kids On the Block: Mirnas Really Do Mattermentioning
confidence: 99%
“…We have previously shown that placental weight is associated with circulating levels of maternal plasma cell-free pregnancy-associated, placentaspecific miRNAs 43 and that labor contraction significantly increases the circulating levels of pregnancy-associated, placenta-specific miRNAs (miR-515-3p, -517a, -517c, and -518b) in maternal plasma. 44 In this study, there was no significant difference in placental weight between the placental abruption and the uncomplicated pregnancy groups. Generally, uterine hypertonus or frequent uterine contractions are seen with placental abruption.…”
Section: Discussionmentioning
confidence: 76%
“…1 Therefore, in placenta abruption, it is possible that the circulating level of plasma cell-free miR-517c (from C19MC) is increased through communication between placental and maternal circulations following uterine contraction. 44 However, there were no significant differences in the maternal plasma levels of other pregnancy-associated, placenta-specific miRNAs (miR-515-3p, -517a, and -518b) between the placental abruption and uncomplicated pregnancy groups. Discrepancies in the plasma concentration of placenta-specific miRNAs within C19MC (increased levels of cell-free miR-517a and decreased levels of cell-free miR-518b) have also been reported in placenta previa pregnancy.…”
Section: Discussionmentioning
confidence: 95%
“…[54][55][56] MicroRNAs have been shown to be very stable in the plasma samples for up to 24 h at room temperature 57,58 and rapidly cleared after the delivery, usually within 24 h after the delivery. 39,40,59,60 In this study, we showed that the degradation of the residual pre-malignant or malignant tissues is accompanied by the continuous decline of circulating C19MC microRNAs, and in case of complete remission of GTD/GTN, extracellular C19MC microRNAs are undetectable in patients' circulation similar as in the circulation of non-pregnant individuals. 39,40 Many cancer treatments work by causing cancer cells to enter an advanced stage of a process known as programmed cell death or apoptosis.…”
Section: Discussionmentioning
confidence: 88%